Technical Efficiency of Poultry Egg Production in Ogun State: A Data Envelopment Analysis (DEA) Approach - Yusuf, S.A.; Malomo, O. (International Journal of Poultry Science, 2007)
The study examines the technical efficiency of poultry egg production in Ogun state using Data Envelopment Analysis (DEA) and OLS regression. The data for the study were collected with the use of well-structured questionnaires from poultry farmers. Average number of birds for small farm size is 301, for medium farm size is 740, while that of large size is 2288. The corresponding net returns were 589, 464.46 and 739.56 per bird per farm respectively. Majority of the farmers are relatively technical efficient in their use of resources, with mean technical efficient being 0.873. Farmers with large farm size are most technical efficient with a mean of 0.8877 followed by medium farm size with a mean of 0.8687 while small farm size has the least mean of 0.8638. The mean input slack for stock, labour and feed are 3.032, 8.942, 0.482 respectively, while the output slack is zero. Years of experience and education have positive effect on technical efficiency at 1 percent while household size negatively affects efficiency at 1 percent. The study concluded that poultry egg production is profitable in the study area and that majority of the farmers are relatively efficient.